Non-market institutions and crime in US counties: Hayek v. Polanyi - Zullo, Roland (Review of Social Economy, 2021)
Karl Polanyi’s The great transformation emphasized the importance of non-market institutions for social equity and stability. In that same era, Friedrich Hayek postulated in The road to serfdom that superior economies were market-based and featured minimal government. I compare these worldviews in relation to property and violent crime. Using US county data, change in crime is modeled as a function of economic structure, economic conditions, and demographics. Consistent with Polanyi, the size of the public sector in the economy negatively associates with crime. Within the public sector, education is a critical crime-reducing function, more so than law enforcement. Industry diversity is positively associated with crime, contrary to Hayek. Manufacturing equates with lower crime and the size of the private non-profit sector is unrelated to crime. Overall the results favor Polanyi’s assertion that non-market institutions are necessary to counter the harsh outcomes arising from market economic systems.
Keywords: H41 (public goods); P17 (capitalism performance); Socialism; Z13 (economic sociology); crime; laissez-faire; non-market institutions; public goods